Basic TT (Truth Table) function for non-computer science students / Saiful Nizam Warris, Syarifah Adilah Mohamed Yusoff and Rozita Kadar - Warris, Saiful Nizam; Mohamed Yusoff, Syarifah Adilah; Kadar, Rozita (Unit Penerbitan JSKM, 2020)
Function is one of the most difficult chapter in programming subject. The difficulty is not only for students but also for academician to deliver the content since it requires of full understanding of the concept of function. Function is where we can break up programs into segments (Mohamad & Mydin , 2019), and according to Ian (2006) is a way of breaking problems down into smaller subproblems and Prinz et. al, (2002) defines function will helps to divide problem into smaller units. Function can be divided into two parts; 1) predefined functions; and 2) user defined functions. Predefined function is the function that already built in and user only need to call the function, but user defined function is the function need to be created by user. The user defined functions is the topic that harder to explain because it has many variable such as function type void or non-void, passing values either using; 1) parameters passing byValue or byRef; 2) global variable. Hence, the student always confuses where to type the input and output statement either in main function main() or user defined function udf().